Identification of Project Construction Delay Factors in Depok City, West Java (Study in Department of Housing and Settlement, Depok City) - Ama Muttahizi Ahadan Auhan; Ayomi Dita Rarasati (International Journal of Applied Business and International Management, 2022)
Depok is one of the big cities in West Java, and it is a buffer zone for the capital city of Indonesia, Jakarta. Hence, the Depok city government is very active in developing the city, especially in building housing and settlements. There are many projects handled by the government but are often delayed. To solve these problems, the purpose of this research is to identify the construction project delay factor. There are 5 variables studied in this study such as project owner factors, contractor factors, consultant factors, shared responsibility factors, and external factors. This research is research with a qualitative approach by conducting a literature review and the results will be validated by experts following the provisions of the Project Management Institute. The results of the analysis show that 5 variables, namely project owner factors, contractor factors, consultant factors, shared responsibility factors and external factors are very valid in influencing construction project delays in Depok City. This research is expected to have positive implications and become a reference in mitigating the risk of delays by determining the control measures for future projects in Depok City and other cities.Â Keywords: Delay, Delay Factor, Construction, Housing Project, Depok